The Effect of Promotion and Service Quality on Customer Interest in Choosing PT. Asuransi Takaful Keluarga Hanifa Agency Bekasi - Wulandari, Seli; Aviantono, Bambang; Freddy, Daulat; Noviarini, Tiara (Peneliti.net, 2025)
This study examines the impact of promotion and service quality on customer interest, utilizing a quantitative approach. Data was collected through questionnaires distributed to 100 respondents, focusing on variables of promotion, service quality, and customer interest. The research employed validity and reliability tests, multiple linear regression analysis, partial (t) and simultaneous (F) tests, and the coefficient of determination (R-Square) to analyze the data. The results show that both promotion and service quality have a significant positive effect on customer interest, with an R-square value of 0.930, indicating that 93% of customer interest is influenced by these two variables. The study concludes that improving promotional strategies and service quality can significantly enhance customer interest, although further research is needed to explore other factors influencing customer behavior.